2022
DOI: 10.3390/microorganisms10050999
|View full text |Cite
|
Sign up to set email alerts
|

Eugenia uniflora L. Silver and Gold Nanoparticle Synthesis, Characterization, and Evaluation of the Photoreduction Process in Antimicrobial Activities

Abstract: Eugenia uniflora linnaeus, known as Brazilian cherry, is widely distributed in Brazil, Argentina, Uruguay, and Paraguay. E. uniflora L. extracts contain phenolic compounds, such as flavonoids, tannins, triterpenes, and sesquiterpenes. The antimicrobial action of essential oils has been attributed to their compositions of bioactive compounds, such as sesquiterpenes. In this paper, the fruit extract of E. uniflora was used to synthesize silver and gold nanoparticles. The nanoparticles were characterized by UV–Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…The peaks at 2924 cm −1 and 2854 cm −1 corresponded to C-H stretching and bending vibrations of CH 3 and CH 2 (alkanes) [ 19 , 28 ]. The bands detected at 1736 cm −1 and 1624 cm −1 were connected to the vibration of C=O from amides and carboxylic groups, and -C=C- aromatic rings, respectively [ 38 ]. The bands at 1452 cm −1 and 1364 cm −1 could be attributed to stretching vibrations of CO of carboxylic acids or esters, to bending vibration of N-H in amides or to stretching vibrations of N-H in secondary amines, or to the C-N stretch vibration of aromatic amines.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 2924 cm −1 and 2854 cm −1 corresponded to C-H stretching and bending vibrations of CH 3 and CH 2 (alkanes) [ 19 , 28 ]. The bands detected at 1736 cm −1 and 1624 cm −1 were connected to the vibration of C=O from amides and carboxylic groups, and -C=C- aromatic rings, respectively [ 38 ]. The bands at 1452 cm −1 and 1364 cm −1 could be attributed to stretching vibrations of CO of carboxylic acids or esters, to bending vibration of N-H in amides or to stretching vibrations of N-H in secondary amines, or to the C-N stretch vibration of aromatic amines.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the development of a standard graph for Qu's absorption at 420 nm in ethanol facilitated quantitative analysis, a valuable tool for determining drug concentrations in solutions. The formulation of Qu nanoparticles demonstrated a high drug entrapment efficiency, ideal particle characteristics for enhanced drug solubility, and stability, as revealed by TEM, zeta potential calculation, and particle size measurement [40][41][42][43]. TEM analysis, conducted at a magnification of 13.0 × 4000 with a scale bar set at 200 nm, offered a detailed view of the selected formulation.…”
Section: Discussionmentioning
confidence: 99%
“…The prominent antimicrobial activity of nanomaterials is closely related to their superfine size. It has been reported that the smaller the particle size, the stronger the antimicrobial activity (Hussain et al, 2019;Franzolin et al, 2022).…”
Section: Characterization Of Nano Silver 331 Tem Analysismentioning
confidence: 99%